Chip Formation Analysis of the Turning of ST41 Steel - Rieza Z Aldio; Muhyi Wahid Saputra; Dedikarni (BRIN, 2022)
ST41 steel is commonly used for the shaft of ships. The shaft tends to corrode due to the interaction with the water. To recycle the used ST41, welding is normally done to repair the damaged or rusted surface of the shaft. The turning process is then conducted to obtain a better surface finish. This research used three types of cutting tools with different geometry at their cutting angle of 800 , 850 , 900 . The chips from the turning process are collected and observed. Chip formation will indicate the quality of the turning process. The chip thickness and formation are observed to determine the effect of the cutting angle on the machining quality. The chip thickness value ranges between 0.13 mm to 0.3 mm, with a cutting angle of 900 producing the thinnest chips and 850 producing the thickest chips. Thicker chips indicate higher cutting force that leads to the wear of cutting tools. The cutting angle also affects obtained the chip formation. Several shapes are obtained, such as long continuous, medium, and short discontinuous shapes. A longer chip means a better process with less chatter on the cutting process. Long continuous chips are dominantly found by using 900 cutting tool. The other two angles are dominated by the discontinuous chips, with a slightly medium length of chips majorly found at 800 and short discontinuous chips recovered using an 850 cutting tool. From this research, it could be known that a 900 cutting angle will produce thinner and better chip formation. Keywords: Chip formation, Chip thickness, Cutting angle, Turning.